HALAL ACCREDITATION AND CERTIFICATION IN A NON-MUSLIM COUNTRY SETTING: INSIGHTS FROM AUSTRALIA HALAL MEAT SUPPLY CHAIN - Zulfakar, Mohd Hafiz; Chan, Caroline; Jie, Ferry; Kaliani Sundram, Veera Pandiyan (International Journal of Supply Chain Management, 2019)
It is a known fact that most halal food products, especially meat are now sourced from various part of the world and the majority of halal food exporters/producers come from non-Muslim countries. This has led to growing concerns from the halal consumers, especially the Muslim communities with regards to whether the halal status of these food products can really be guaranteed throughout the supply chain in these countries and whether the halal foods claimed are authentic. This study aims to better understand the current halal meat certification in Australia, a predominantly non-Muslim country. By adopting a case study approach, this study uses semi structured interviews and field observations as the primary methods of data collection. Fifteen participants representing the halal certifiers and meat processors participated in this study. This study is one of the first to identify and discuss conceptually the operations of halal meat supply chain in Australia. It has contributed to the body of knowledge through an understanding of the issues that are affecting halal meat supply chain operations in a non-Muslim majority environment.